Endovascular Treatment of Medial Tentorial Dural Arteriovenous Fistula Through the Dural Branch of the Pial Artery - Chu, Chan-Lin; Chu, Yu-Cheng; Lam, Chee-Tat; Lee, Tsong-Hai; Chien, Shih-Chao; Yeh, Chih-Hua; Wu, Yi-Ming; Wong, Ho-Fai (Frontiers in Neurology, 2021)
Background: Tentorial dural arteriovenous fistula is a rare subtype of intracranial dural arteriovenous fistula (DAVF) with a deteriorating natural course, which may be attributed to its pial angioarchitecture. TDAVF often harbors feeders arising from pial arteries (FPAs). Reports have revealed that, if these feeders are not obliterated early, the restricted venous outflow during the embolization process may cause upstream congestion in the fragile pial network, which increases the risk of hemorrhagic complications. Because most reported cases of TDAVF were embolized through feeders from non-pial arteries (FNPAs), little is known of the feasibility of direct embolization through FPAs. Methods: We present three patients with medial TDAVFs that were embolized through the dural branches of the posterior cerebral and superior cerebellar arteries. Findings from brain magnetic resonance imaging, computed tomography, angiography, and clinical outcomes are described. Furthermore, we performed a review of the literature on TDAVFs with FPAs. Results: The fistulas were completely obliterated in two patients; both recovered well with no procedure-related complications. The fistula was nearly obliterated in one patient, who developed left superior cerebellum and midbrain infarct due to the reflux of the embolizer into the left superior cerebellar artery. Including our cases, eight cases of TDAVFs with direct embolization through the FPAs have been reported, and ischemic complications occurred in three (37.5%). Conclusions: Advancing microcatheter tips as close to the fistula point as possible and remaining highly aware of potential embolizer flow back into the pial artery are key factors in achieving successful embolization. Balloon-assisted embolization may be an option for treating TDAVFs with FPAs in the future.